Wernicke’s encephalopathy: obstetric diagnostic challenge! (a rare complication of hyperemesis gravidarum): a case report and review of literature - N., Sunanda; Impana M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Wernicke’s encephalopathy (WE) is an acute neurological disorder caused by a deficiency in thiamine. It is characterized by triad of altered mental status, ataxia and ophthalmoplegia. Most of the cases reported were secondary to long-term alcohol use. We reported a rare case of WE due to hyperemesis gravidarum in a 29-year-old P1L1A1 women at 22 weeks of gestation who had spontaneous abortion. Patient manifested with features of mental confusion, nystagmus, and gait ataxia. Diagnosis was established after MRI findings suggestive of WE in thalamus. Patient clinically improved after treatment with thiamine. We emphasize the importance of thiamine supplementation to women with hyperemesis to prevent life threatening complications.